COLOUR DOPPLER INDICES OF OVARIAN ARTERY IN RELATION TO OVARIAN ACTIVITY IN CROSSBRED CATTLE - SATHESHKUMAR, S; SIVAKUMAR, A; RAJA, S; JAYAGANTHAN, P; PRABAHARAN, V; RAJASUNDARAM, RC (The Indian Journal of Animal Reproduction, 2017)
Crossbred cattle exhibiting estrus or post-partum anestrus were subjected to colour doppler ultrasonography to evaluate the blood flow parameters viz., peak systolic velocity (PSV), end diastolic velocity (EDV), pulsatility index (PI), resistivity index (RI) and doppler pulse duration (DPD). The comparison of blood flow parameters of cattle in estrus (n=12) revealed that PSV and DPD indices in dominant follicle and ipsilateral ovarian artery were highly correlated (p<0.05). The blood flow assessment of ovarian artery in anestrus (n=9) and estrus (n=9) cattle suggested higher (p<0.05) values of PI, RI and DPD in anestrus cattle. In brief, anestrus crossbred cattle had deficient blood flow in ovarian artery as indicated by low velocity, increased flow resistance and slow pulsation.